2009
DOI: 10.21432/t2m88c
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Knowledge-Building Discourse: An Analysis of Online Discussions in Mainstream and Honours Social Studies Courses

Abstract: Questions about the suitability of cognitively-oriented instructional approaches for students of different academic levels are frequently raised by teachers and researchers. This study examined student participation in knowledge-building discourse in two implementations of a short inquiry unit focusing on environmental problems. Participants in each implementation consisted of students taking a mainstream or an honours version of a tenth grade social studies course. We retrieved data about students’ actions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…In the last two decades, knowledge building has been shown to enhance the performance and learning of learners of various ages (Chuy et al 2010;Niu and van Aalst 2009;So et al 2010; van Aalst and Truong 2011;Zhang et al 2007;Authors 2014). However, can knowledge building benefit students with low achievement?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, knowledge building has been shown to enhance the performance and learning of learners of various ages (Chuy et al 2010;Niu and van Aalst 2009;So et al 2010; van Aalst and Truong 2011;Zhang et al 2007;Authors 2014). However, can knowledge building benefit students with low achievement?…”
Section: Introductionmentioning
confidence: 99%
“…They found that portfolio assessment guided by knowledge-building principles had a more positive influence on students' conceptual understanding than portfolio assessment without a foundation in knowledge-building principles, and that this influence was stronger for students with lower achievement. Niu and van Aalst (2009) measured the benefits of knowledge building for both honors students and students in regular classes at a Canadian high school. The students in the honors class outperformed those in the regular class, but the within-class differences were larger than the between-class differences.…”
Section: Introductionmentioning
confidence: 99%
“…The starting point for its analysis is the framework proposed by van Aalst (2009), which distinguishes between knowledge sharing, knowledge construction, and knowledge building/creation discourses, and highlights the similarities and differences among the major learning theories in CSCL. Knowledge sharing is underpinned by an understanding of learning as the transmission of ideas.…”
Section: Introductionmentioning
confidence: 99%
“…To build on what is known about the characteristics of online discourse, we adapted the coding scheme of content analysis developed by van Aalst (2009). We aimed to develop discourse patterns and show the variety of ways in which students go about their collaborative interactions online.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation